An analysis of the CatWalk XT and a composite score to assess neurofunctional deficits after photothrombosis in mice. (23rd April 2021) - Bärmann, J.; Walter, H.L.; Pikhovych, A.; Endepols, H.; Fink, G.R.; Rueger, M.A.; Schroeter, M.
Highlights: The proposed neuroscore allows reliable specification and quantification of motorfunctional deficits after photothrombosis. Neuroscore detects asymmetry of limbs until 16 days after photothrombosis. CatWalk XT is inferior in detecting asymmetric motor deficits. CatWalk XT does detect gait speed changes. Abstract: The purpose of this study was to evaluate CatWalk's capability for assessing the functional outcome after photothrombotic stroke affecting the motor cortex of mice. Mice were tested up to 21 days after photothrombosis or sham surgery using CatWalk, and a composite score assessing functional deficits (neuroscore). The neuroscore demonstrated deficits of the contralateral forelimb for more than two weeks after stroke. There were no asymmetric or coordinative dysfunctions of limbs detected by CatWalk. However, CatWalk data revealed impairment of locomotion speed and its depending parameters for one-week after stroke in strong correlation to the neuroscore. Data suggest that the composite neuroscore allows to more sensitively and precisely specify and quantify photothrombosis-induced hemisyndromes than CatWalk.